2018
DOI: 10.29252/joge.2.4.64
|View full text |Cite
|
Sign up to set email alerts
|

Self-care and its predictive role in the quality of life of the elderly living in the community

Abstract: Introduction: Quality of life is one of the important issues in today's health care. Despite the high importance of self-care and quality of life in improving the health of the elderly, unfortunately, this issue has not been sufficiently addressed in Iran. The aim of this study was to determine the predictive value of self-care capacity of elderly people in improving their quality of life in Bojnourd in 2017. Method: This is a descriptive-analytical study that was carried out by sampling 180 elderly people usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This finding was consistent with the findings of Rabie & Klopper (2015) studies that self-care in the elderly is low [18]. This finding is consistent with the results obtained in the study of SangSefidi et al [14] and Avazeh et al [13]. However, in the study of Anbari et al, the subjects had a semi-desirable self-care ability [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding was consistent with the findings of Rabie & Klopper (2015) studies that self-care in the elderly is low [18]. This finding is consistent with the results obtained in the study of SangSefidi et al [14] and Avazeh et al [13]. However, in the study of Anbari et al, the subjects had a semi-desirable self-care ability [19].…”
Section: Discussionsupporting
confidence: 91%
“…The results of various studies show that self-care ability is low in the elderly [13]. In the study by SangSefdi et al, the self-care ability of most of the elderly living in Bojnord city was low, and women had a lower level of self-care than men [14]. Prochota et al (2019) concluded that mental health is directly related to self-care.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings in Bojnord showed that older men have higher self-care abilities than older women. 17 The results of Salehi and Keikavoosi-Arani's study also indicated a correlation between gender and occupational self-care in the elderly and a correlation between genders. This difference is because jobs are more important for men.…”
Section: Discussionmentioning
confidence: 90%
“…Self-care encompasses a wide range of areas like prevention, improving undesirable lifestyles, better acceptance and compliance with the treatment of diseases, prevention of secondary effects of physical and mental problems, and generally reducing the costs of medical services [19][20][21][22]. According to surveys conducted in different countries, on average, 40 to 60 percent of older adults who have a low level of self-care need the help of others to perform their daily activities [23][24][25][26][27]. The results of some studies indicated a signi cant correlation between the two variables of self-care and well-being [28,29].…”
Section: Introductionmentioning
confidence: 99%